Distinct subcircuits within the mesolimbic dopamine system encode the salience and valence of social stimuli - Erica A. Cross; Johnathan M. Borland; Emma K. Shaughnessy; Susan D. Lee; Vivian Vu; Elizabeth A. Sambor; Robert L Meisel; Kim L. Huhman; H. Elliott Albers (Psychopharmacology, 2025)

Subduction zone-related metasomatism of Devonian oceanic lithosphere: Evidence from mineralogical, geochemical, and O-H-Sr isotope characteristics of amphibole-bearing peridotites of the Sowie Mountain Block (SW Poland) - Ahmed H. Ahmed; Mohamed M. Hamdy; Thomas C. Meisel (Lithos, 2024)

Temperature‐dependent effects of house fly proto‐Y chromosomes on gene expression could be responsible for fitness differences that maintain polygenic sex determination - Kiran Adhikari; Jae Hak Son; Anna H. Rensink; Jaweria Jaweria; Daniel Bopp; Leo W. Beukeboom; Richard P. Meisel (Molecular Ecology, 2021)
Sex determination, the developmental process by which sexually dimorphic phenotypes are established, evolves fast. Evolutionary turnover in a sex determination pathway may occur via selection on alleles that are genetically linked to a new master sex determining locus on a newly formed proto‐sex chromosome. Species with polygenic sex determination, in which master regulatory genes are found on multiple different proto‐sex chromosomes, are informative models to study the evolution of sex determination and sex chromosomes. House flies are such a model system, with male determining loci possible on all six chromosomes and a female‐determiner on one of the chromosomes as well. The two most common male‐determining proto‐Y chromosomes form latitudinal clines on multiple continents, suggesting that temperature variation is an important selection pressure responsible for maintaining polygenic sex determination in this species. Temperature‐dependent fitness effects could be manifested through temperature‐dependent gene expression differences across proto‐Y chromosome genotypes. These gene expression differences may be the result of cis regulatory variants that affect the expression of genes on the proto‐sex chromosomes, or trans effects of the proto‐Y chromosomes on genes elswhere in the genome. We used RNA‐seq to identify genes whose expression depends on proto‐Y chromosome genotype and temperature in adult male house flies. We found no evidence for ecologically meaningful temperature‐dependent expression differences of sex determining genes between male genotypes, but we were probably not sampling an appropriate developmental time‐point to identify such effects. In contrast, we identified many other genes whose expression depends on the interaction between proto‐Y chromosome genotype and temperature, including genes that encode proteins involved in reproduction, metabolism, lifespan, stress response, and immunity. Notably, genes with genotype‐by‐temperature interactions on expression were not enriched on the proto‐sex chromosomes. Moreover, there was no evidence that temperature‐dependent expression is driven by chromosome‐wide cis ‐regulatory divergence between the proto‐Y and proto‐X alleles. Therefore, if temperature‐dependent gene expression is responsible for differences in phenotypes and fitness of proto‐Y genotypes across house fly populations, these effects are driven by a small number of temperature‐dependent alleles on the proto‐Y chromosomes that may have trans effects on the expression of genes on other chromosomes.

Increases in temperature and nutrient availability positively affect methane‐cycling microorganisms in Arctic thermokarst lake sediments - Anniek E. E. de Jong; Michiel H. in ’t Zandt; Ove H. Meisel; Mike S. M. Jetten; Joshua F. Dean; Olivia Rasigraf; Cornelia U. Welte (Environmental Microbiology, 2018)
Summary Arctic permafrost soils store large amounts of organic matter that is sensitive to temperature increases and subsequent microbial degradation to methane (CH 4 ) and carbon dioxide (CO 2 ). Here, we studied methanogenic and methanotrophic activity and community composition in thermokarst lake sediments from Utqiag˙vik (formerly Barrow), Alaska. This experiment was carried out under in situ temperature conditions (4°C) and the IPCC 2013 Arctic climate change scenario (10°C) after addition of methanogenic and methanotrophic substrates for nearly a year. Trimethylamine (TMA) amendment with warming showed highest maximum CH 4 production rates, being 30% higher at 10°C than at 4°C. Maximum methanotrophic rates increased by up to 57% at 10°C compared to 4°C. 16S rRNA gene sequencing indicated high relative abundance of Methanosarcinaceae in TMA amended incubations, and for methanotrophic incubations Methylococcaeae were highly enriched. Anaerobic methanotrophic activity with nitrite or nitrate as electron acceptor was not detected. This study indicates that the methane cycling microbial community can adapt to temperature increases and that their activity is highly dependent on substrate availability.

Calcium Microcrystal Formation in Recurrent Herniation Patients After Autologous Disc Cell Transplantation - S. Schwan; C. Ludtka; A. Friedmann; T. Mendel; H. J. Meisel; A. Heilmann; I. Kaden; F. Goehre (Tissue Engineering and Regenerative Medicine, 2017)

GGOS-D: homogeneous reprocessing and rigorous combination of space geodetic observations - M. Rothacher; D. Angermann; T. Artz; W. Bosch; H. Drewes; M. Gerstl; R. Kelm; D. König; R. König; B. Meisel; H. Müller; A. Nothnagel; et al. (Journal of Geodesy, 2011)

Brain antigens in functionally distinct antigen-presenting cell populations in cervical lymph nodes in MS and EAE - Marloes van Zwam; Ruth Huizinga; Marie-José Melief; Annet F. Wierenga-Wolf; Marjan van Meurs; Jane S. Voerman; Knut P. H. Biber; Hendrikus W. G. M. Boddeke; Uta E. Höpken; Christian Meisel; Andreas Meisel; Ingo Bechmann; et al. (Journal of Molecular Medicine, 2009)

Diverse contributing sources to chromitite petrogenesis in the Shebenik Ophiolitic Complex, Albania: evidence from new PGE- and Os-isotope data - H. Kocks; F. Melcher; T. Meisel; K.-P. Burgath (Mineralogy and Petrology, 2007)

Possible role of MDR1 two-locus genotypes for young-age onset ulcerative colitis but not Crohn’s disease - T. Fiedler; C. Büning; W. Reuter; G. Pitre; E. Gentz; HH. Schmidt; J. Büttner; J. Ockenga; T. Gerloff; C. Meisel; H. Lochs; I. Roots; et al. (European Journal of Clinical Pharmacology, 2007)

Repeated quinpirole treatments produce neurochemical sensitization and associated behavioral changes in female hamsters - Julia A. Chester; Amanda J. Mullins; Chau H. Nguyen; Val J. Watts; Robert L. Meisel (Psychopharmacology, 2006)

Nucleocapsid protein of cell culture-adapted Seoul virus strain 80–39: Analysis of its encoding sequence, expression in yeast and immuno-reactivity - Jonas Schmidt; Burkhard Jandrig; Boris Klempa; Kumiko Yoshimatsu; Jiro Arikawa; Helga Meisel; Matthias Niedrig; Christian Pitra; Detlev H. Krüger; Rainer Ulrich (Virus Genes, 2005)

First Molecular Evidence for Puumala Hantavirus in Slovakia - K. Leitmeyer; C. Sibold; H. Meisel; R. Ulrich; M. Labuda; D.H. Krüger (Virus Genes, 2001)

Polymorphism of the N -acetyltransferase ( NAT2 ), smoking and the potential risk of periodontal disease - P. Meisel; Ramona Timm; H. Sawaf; Jutta Fanghänel; Werner Siegmund; T. Kocher (Archives of Toxicology, 2000)

First Case of Infection with Hantavirus Dobrava in Germany - H. Meisel; Å. Lundkvist; K. Gantzer; W. Bär; C. Sibold; D. H. Krüger (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Coding strategy of the S and M genomic segments of a hantavirus representing a new subtype of the Puumala serotype - A. Reip; B. Haring; C. Sibold; R. Stohwasser; E. K. F. Bautz; G. Darai; H. Meisel; D. H. Krger (Archives of Virology, 1995)

Detection ofBacteroides fragilis endotoxin in amniotic fluid by counterimmunoelectrophoresis - I. Beckmann; K. de Graaff; F. Meisel-Mikołajczyk; H. C. S. Wallenburg (Antonie van Leeuwenhoek, 1994)

Comparison of three different recombinant hepatitis B virus core particles expressed inEscherichia coli - Anke Maaen; Annett Rehfeldt; S. Kieig; A. Ladhoff; W. E. Hhne; Helga Meisel (Archives of Virology, 1994)

The effects of deoxycholate and sodium dodecyl sulphate on the serological reactivity of antigens isolated from six Bacteroides reference strains - I. Beckmann; F. Meisel-Mikolajczyk; H. C. S. Wallenburg (Antonie van Leeuwenhoek, 1990)